Applications of advances in mRNA-based platforms as therapeutics and diagnostics in reproductive technologies - Bafleh, Wjdan S.; Abdulsamad, Haia M. R.; Al-Qaraghuli, Sally M.; El Khatib, Riwa Y.; Elbahrawi, Rawdah Taha; Abdukadir, Azhar Mohamud; Alsawae, Shaima M.; Dimassi, Zakia; Hamdan, Hamdan; Kashir, Junaid (Frontiers in Cell and Developmental Biology, 2023)
The recent COVID-19 pandemic led to many drastic changes in not only society, law, economics, but also in science and medicine, marking for the first time when drug regulatory authorities cleared for use mRNA-based vaccines in the fight against this outbreak. However, while indeed representing a novel application of such technology in the context of vaccination medicine, introducing RNA into cells to produce resultant molecules (proteins, antibodies, etc.) is not a novel principle. It has been common practice to introduce/inject mRNA into oocytes and embryos to inhibit, induce, and identify several factors in a research context, while such aspects have also been proposed as potential therapeutic and diagnostic applications to combat infertility in humans. Herein, we describe key areas where mRNA-based platforms have thus far represented potential areas of clinical applications, describing the advantages and limitations of such applications. Finally, we also discuss how recent advances in mRNA-based platforms, driven by the recent pandemic, may stand to benefit the treatment of infertility in humans. We also present brief future directions as to how we could utilise recent and current advancements to enhance RNA therapeutics within reproductive biology, specifically with relation to oocyte and embryo delivery.